PEMANFAATAN TEPUNG LIMBAH IKAN GABUS PASIR (Butis amboinensis) SEBAGAI SUBSTITUSI TEPUNG IKAN DALAM RANSUM TERHADAP PEFORMANS ITIK LOKAL UMUR 35 MINGGU - INDRA TARIGAN (Jurnal Peternakan Integratif, 2015)
ABSTRACT INDRA DAT PERDANA TARIGAN, 2015: “ Utilization of Gabus Pasir (Butis amboinensis)waste meal In Ration Against Peformance of Laying Duck 35th Week of Age”, guided by R. EDHY MIRWANDHONO and TRI HESTI WAHYUNI. This research was conducted at Desa Lama Kecamatam Hamparan Perak Kabupaten Deli Serdang from Mart to June 2015. This study aimed to determine the effect of Gabus Pasir waste meal in the ration on duck-day, egg weight and FCR. The design used in this research is completely randomized design (CRD) with three treatments and 6 replications, each replication consisted  of 4 laying ducks. Treatmen consists of P0 (feed without Gabus Pasir waste meal); P1 (feed with Gabus Pasir waste meal as much as 5%); P2 (feed with Gabus Pasir waste meal as much as 10%). The results showed the average of duck-day percentage such as 55,87; 58,52 dan 61,17, respectivly. Egg weight (g) such as 63,73; 64,09 and 64,22, respectivly. FCR such as 5,98; 5,66 and 5,34, respectivly. The results showed that the treatment was not significant effect on duck-day, egg weight and feed conversion. The conclusion of this research that Gabus Pasir waste meal can be used in ration to the level of 10%. Keywords: Gabus Pasir waste meal, Peformance of Laying duck